KEARIFAN LOKAL (LOCAL GENIUS) SEBAGAI SOKO GURU MENATA PERADABAN BANGSA YANG BERKARAKTER NUSANTARA (REFLEKSI KARYA KI DALANG TANGSUB) - I Made Suarta (JURNAL IKADBUDI, 2013)
Local knowledge (local genius) is the quintessence of our ancestors thinking either oral or written traditions which we have received to date. Thought that, in the context of real archipelago has the same thread, which has a valuable values and universal to strengthen the integrity of the Unitary Republic of Indonesia. Through our founding genius thought that we should be able to implement it in real life to be able to reach people who "Gemah ripah loh jinawi", no less clothing, food, and shelter!Some of the many concepts of mind for the people of Bali are reflected in the work of puppeteer Ki Dalang Tangsub contributed to the development of Indonesia and has a universal value is the concept of maintaining the environment, save money, and humble. Through mental attitude has not always feel pretty; like not smart enough, not skilled enough, and not mature enough experience, make us always learn and practice. Learn and continue lifelong learning will make a man more mature and a lot of experience. Thus, the challenges in life will be easy to overcome. All that will be achieved, in addition to the hard work is also based on the mental attitude of inferiority is not proud, haughty, arrogant and other negative attitudes. Thought care environment, managing finances, and humble as described above, in Bali has been formulated through a literature shaped geguritan, namely Geguritan I Gedé Basur Dalang Tangsub works, one of the great authors in the early 19th century.  Keywords: Local knowledge, a cornerstone of, the character of the archipelago